Exosome: The Regulator of the Immune System in Sepsis - Qiu, Peng; Zhou, Jing; Zhang, Jin; Dong, Youjing; Liu, Yang (Frontiers in Pharmacology, 2021)
Sepsis is a syndrome comprised of a series of life-threatening organ dysfunctions caused by a maladjusted body response to infection with no effective treatment. There is growing evidence that the immune system plays a core role in sepsis. Pathogens cause abnormal host immune response and eventually lead to immunosuppression, which is an important cause of death in patients with sepsis. Exosomes are vesicles derived from double invagination of plasma membrane, associating with immune responses closely. The cargos delivered by exosomes into recipient cells, especially immune cells, effectively alter their response and functions in sepsis. In this review, we focus on the effects and mechanisms of exosomes on multiple immune cells, as well as the role of immune cell-derived exosomes in sepsis. This is helpful for us to have an in-depth understanding of the mechanism of immune disorders in sepsis. Exosomes is also expected to become a novel target and therapeutic approach for sepsis.